2012
DOI: 10.1021/jp207296h
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Empirical Equation in Extracting Disorder Parameters in Inhomogeneous Organic Thin Films

Abstract: Monte Carlo simulation of charge transport is employed to test the suitability of extensively used empirical equations, proposed by Gaussian disorder model (GDM)/ correlated disorder model (CDM), for extracting disorder parameters from the field and temperature dependence of mobility in inhomogeneous organic thin films. Numerous observations suggests that the effective energetic disorder seen by the carrier in an inhomogeneous system decreases with increase in concentration of low disordered regions. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(34 citation statements)
references
References 44 publications
1
33
0
Order By: Relevance
“…However, as previously noted from Figure 3(a) the response of σ GDM is not as sensitive as σ DOS to the introduction of local order where it is typically found that to achieve a 50% reduction in σ GDM relative to the DG reference magnitude it is necessary for C to exceed about 0.9 for n/N > 0.3. Similar behaviour has been reported in independent Monte Carlo studies [13][14][15] which was attributed to weakly percolating transport where the majority of carriers follow low-mobility paths through NOC sites. The preference to hop via the NOC sites is clearly understood with reference to Figure 4 where it is noted that after the injected carriers have had an opportunity to thermalise they will tend to occupy the lowest energy states associated with the σ DOS (NOC) tail.…”
Section: Simulation Of Dipolar Glassessupporting
confidence: 86%
See 1 more Smart Citation
“…However, as previously noted from Figure 3(a) the response of σ GDM is not as sensitive as σ DOS to the introduction of local order where it is typically found that to achieve a 50% reduction in σ GDM relative to the DG reference magnitude it is necessary for C to exceed about 0.9 for n/N > 0.3. Similar behaviour has been reported in independent Monte Carlo studies [13][14][15] which was attributed to weakly percolating transport where the majority of carriers follow low-mobility paths through NOC sites. The preference to hop via the NOC sites is clearly understood with reference to Figure 4 where it is noted that after the injected carriers have had an opportunity to thermalise they will tend to occupy the lowest energy states associated with the σ DOS (NOC) tail.…”
Section: Simulation Of Dipolar Glassessupporting
confidence: 86%
“…Simulations with local ordering have been performed to model both DGs and MDPs. This work extends independent previous Monte Carlo studies which have either considered short-range order in MDPs using non-correlated random orientation vectors [12], or have examined the effect of introducing ordered regions into DG energy landscapes by using pre-determined Gaussian distributions to perform the allocation of site energies [13][14][15]. By contrast the generation of energy landscapes in the present study has been achieved using a fundamental electrostatic calculation of the dipole potential, where local variations of the potential have been introduced using dipoles that are locally ordered within cubic regions that have a specified volume.…”
Section: Introductionmentioning
confidence: 60%
“…For italickT=0.4σ, energies around ϵdif=5σ were present in the simulations, and thus results for italickT0.4σ can be considered as reliable for the lattice of 7003 sites. Too small numbers of sites N in simulated arrays is a common problem of Monte Carlo simulations of the effects related to carrier diffusion in a Gaussian DOS (). We discuss the consequences of the finite‐size effects for simulations as well as for real samples in Sections 9 and 10, respectively.…”
Section: Dependence Of Transport Coefficients On Electric Field Fmentioning
confidence: 99%
“…The physical justification for such a proposal is linked to the energy landscape that is generated by the localised alignment of TPD dipoles. Carrier transport through such dipolar landscapes is believed to proceed via a hopping mechanism and energetic barriers are anticipated to exist at crystalline-amorphous interfaces [10,11]. As TPD is a unipolar hole conductor, the photogeneration of electron-hole pairs will result in a population of mobile hole carriers (p), and a population of immobile electrons (n) that are distributed across crystalline (n c ) and amorphous (n a ) TPD sites.…”
Section: Resultsmentioning
confidence: 99%